Integrasi Sumber Energi Terbarukan dalam Pemanfaatan Sumber Daya Nikel di Luwu Timur - Dewa Nugroho, Arya; Supriyadi, Imam; Thamrin, Suyono; Sidik Boedoyo, Mohamad (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2023)
East Luwu Regency is one of the areas in South Sulawesi which has quite large natural resource potential, including mineral resources such as nickel. However, the need for energy to run this industrial sector is a challenge in itself, especially in terms of supplying environmentally friendly energy. This study aims to analyze the potential of renewable energy sources in the region and how their use can reduce dependence on fossil energy sources and environmental pathways generated by the nickel mining industry. The research method used is a qualitative method with Focused Group Discussion (FGD). The results of the study show that the integration of renewable energy sources such as hydroelectric power plants (PLTA) and microgrid infrastructure has great potential in the utilization of nickel resources in East Luwu.